KETERKAITAN INFLASI, SUKU BUNGA KREDIT, DAN TINGKAT PENGANGGURAN TERHADAP KREDIT BERMASALAH PADA BANK UMUM DI INDONESIA - Nindita, Divya Ratna; Kaluge, David (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aimed to analyze relationship beetween Non Performing Loan (NPL), inflation, lending rate, and rate of unemployment. Credit by conventional banks always carry Non Performing Loan. The more amount of credit granted, will carry the higher risk. Indonesian Banking system has been implementing selective credit policy. This selectivity seen from conditions of credit requirement for different categories. This article use Autoregressive Distributed Lag Error Correction Model by Engle Granger to analyze the relationship on the short term and long term. The result showed that in long run, inflation, lending rates, and rate of unemployment has a significant effect in NPL working capital loans, but inflation and rate of unemployment doesnâ€™t have significant effect in NPL investment loans. In the short term,inflation has no effect on both NPL investment and NPL working capital, and rate of unemployment has a significant effect in NPL working capital loans in short term. Â  Key Words: NPL, Investment Loans, Working Capital, ECM